Gagasan, Tantangan dan Prospek Investasi Syari'ah dalam Pertarungan Politik Ekonomi Global - Anzu Elvia Zahara T (NALAR FIQH: Jurnal Hukum Islam, 2011)
Efforts towards the Islamic community that need to be mached by entering into the discourse of the Islamic financial market and derivatives instruments. In fact Islamic financial market in needed by muslim in Islamic investment activities for the prevention of gharar and riba. However, these financial instrument is still a lot of pros and cons among muslim figures. As to which badawis statement; The price meaning of gharar it self uncertain. The literature does not give us an agreed definition and scholars rely more in enumering, individual instance of gharar as substitute of precise definition of term.